The Vilnius Cultural Borderland as a Location and a Space of Experience for a Young Generation of Polish Youth: Socio-Cultural (Self-)Identification - Szerląg, Alicja (Acta Paedagogica Vilnensia, 2019)
Locations and spaces possess socio-cultural connotations, which is why they play a significant role in the processes of experiencing and cultural (self-)identification. That is because in the conditions specific for them and in relation to the symbolic attributes, an individual conceptualizes their own rationality, and on its basis their interpretative perspective, thanks to which, through participation in meaningful locations, they (self-)identify culturally. Roots, connection, and identification within a meaningful location constitute, therefore, significant creators of individual identification and the creation of a community. The meaningful location, in the above context, is the Vilnius region, identified by its inhabitants – young Poles – as a meaningful location: a little homeland. Taking into account its specific attributes, one might consider the faces of the Vilnius region: the physical, the mental, and the interactive-communicative ones. There are cultural differences in each of them, which assign the location a certain multicultural and intercultural specificity. As a result, the participation of young Poles in the location results in a multidimensional experiencing (cognitive, emotional, and action-related) of affirmative character, decisive in the formation of their cultural (self-)identification. On the basis of conducted empirical research, three fundamental scopes of the (self-)identification can be defined: the national, the socio-cultural, and the intercultural ones. Young Poles have a significant potential in the area of the formation of a multi-range and multidimensional identity of a borderland, as well as the construction of a community at the point of contact of cultures, citizenships, and multiculturality perceived as a factor in the development of the culture of peace. All of these factors constitute an important reference for education.